2000
DOI: 10.1111/j.1467-842x.2000.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Age at first intercourse in an Australian national sample of technical college students

Abstract: Objective : This study aims to broaden the current body of knowledge regarding the sexual behaviour of young Australians by examining the age and correlates of age of first intercourse in a national sample of Technical and Further Education apprentices. Method : In 1995, students at randomly selected technical colleges in Australia were surveyed on HIV‐related issues. Questionnaires were administered to a stratified cluster sample of automotive, hairdressing and commercial cookery apprentices. Respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
10
1
2
Order By: Relevance
“…(21) Studies reporting age at first sex specifically in Indigenous youth across Australia are limited. Studies of the general Australian population (22)(23)(24)(25)(26) have reported median ages at first sex as 16 to 18 years compared to our study which reported 15 years as the median age at first sex. The GOANNA study, a large multicentre survey of young Indigenous people's sexual knowledge and behaviours, reported a similar median age at first sex to our study.…”
Section: Discussioncontrasting
confidence: 88%
“…(21) Studies reporting age at first sex specifically in Indigenous youth across Australia are limited. Studies of the general Australian population (22)(23)(24)(25)(26) have reported median ages at first sex as 16 to 18 years compared to our study which reported 15 years as the median age at first sex. The GOANNA study, a large multicentre survey of young Indigenous people's sexual knowledge and behaviours, reported a similar median age at first sex to our study.…”
Section: Discussioncontrasting
confidence: 88%
“…Furthermore, 30-50% of adolescents under 17 years of age have reported having sexual intercourse (Abma, Martinez, Mosher, & Dawson, 2004;Grunseit & Richters, 2000;Kaestle, Halpern, Miller, & Ford, 2005;Leigh, Morrison, Trocki, & Temple, 1994). Behaviors such as having sex for the first time in earlier adolescence, infrequently using condoms, and having a higher number of sexual partners have been shown to be associated with sexually transmitted diseases in representative samples in Britain and in the U.S. (Fenton et al, 2001;Kaestle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the experience of tongue kissing with a regular or casual partner was very common (around 80% of respondents), less than 60% of these first-year students had experienced oral sex or vaginal intercourse. This was a considerably lower proportion having sexual experience by their late teens than other groups in Australia such as technical college students, among whom 83% of 18-year-olds had had intercourse in 1995 (Grunseit & Richters, 2000). Among prison inmates, 46% had had intercourse before they turned 15 (Butler, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of young people focus on sexual risk for sexually transmitted infection or pregnancy rather than on types of sexual practice (Brener et al, 2002). In Australia, there have been numerous surveys of high school (Cubis, Lewin, & Raphael, 1985;Dunne, Donald, Lucke, Nilsson, & Raphael, 1993;Dunne et al, 1994;Kang & Zador, 1993;, 1999 and university students (Rosenthal, Smith, Reichler, & Moore, 1996;Turtle et al, 1989) and a few of other young people (Grunseit & Richters, 2000;Hillier et al, 1998;Tresidder, 2003), but few surveys have been repeated over an extended period to allow an analysis of change over time (Rosenthal et al, 1996;Rosenthal, Smith, & Lindsay, 1998). Cubis et al (1985) focused on predictors of pregnancy rather than on sexual practice in general, though non-coital practice was mentioned, dividing sexual experience into "major" (i.e., intercourse) and "minor" in answer to the question "Have you had any sexual experience with a partner other than intercourse (e.g., cuddling, petting, etc.)?"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation